PERANCANGAN SISTEM INFORMASI AKUNTANSI PADA SIKLUS PENDAPATAN DAN PENGELUARAN UNTUK MENINGKATKAN KUALITAS INFORMASI TOKO EMAS X DI SURABAYA - Ardhyanata Ardhyanata; Adhicipta Raharja Wirawan (Perpustakaan Universitas Surabaya, 2018)
X Gold Shop is one of the MSMEs which engaged in the sale and purchase of gold jewelry and became the object of this research. Like the majority of MSMEs, X Gold Shop is still using manual system to record its business transactions and does not make reports about the business operations. Without the processing of information, of course the business entity has no guidance in decision making. This research is intended to design a computerized accounting information system at X Gold Shop to improve the quality of information through the report features in Bee Toko Emas software. This research use interview and observation method to collect data related toX Gold Shop and jewelry pricing. The result of this research is Bee Toko Emas software is able to process information related to business transaction into reports, both accounting and managerial reports, which are capable of supporting decision-making process for X Gold Shop.